Damus-Kay-Stansel procedure with ventricular septal defect enlargement. (June 2021) - Nakata, Tomohiro; Tachi, Maiko; Yasuda, Kenji; Nakashima, Shigeki; Minamoto, Toshiko; Oda, Teiji
A full-term infant who had tricuspid atresia with transposed great arteries, a ventricular septal defect, subpulmonary stenosis with posterior malalignment of the conus septum, bicuspid pulmonary valve, and a high-takeoff left coronary artery was referred to our institution. The subpulmonary stenosis gradually progressed and cyanosis worsened. We successfully performed a Damus-Kay-Stansel procedure and a bidirectional Glenn shunt concomitant with ventricular septal defect enlargement. The conus septum was resected along with thick fibrous tissue through both semilunar valves (without ventriculotomy). Postoperative echocardiography demonstrated that both the ventricular septal defect and the subpulmonary space were enlarged effectively without semilunar valve regurgitation.